Late-career Risks in Changing Welfare States: Comparing Germany and the United States since the 1980s - Jan Paul Heisig (Amsterdam University Press, 2015)
Motivated by debates about welfare state retrenchment and growing economic insecurity, this book takes a closer look at the situation of older workers in Germany and the US. It first provides an in-depth account of country differences in key social programs - and of crucial changes since the 1980s. To better understand the impact of these changes on the lives of ordinary citizens, the second part of the book uses household panel data to examine the changing financial consequences of late-career job loss and retirement. Income losses due to men's retirement have grown in both countries, consistent with gradual declines in the generosity of public pension schemes and other public programs. In the US, income trajectories have also become more heterogeneous, with more workers suffering very large income losses and having low income after retirement. Changes in employer-sponsored pensions, in particular the rise of defined-contribution plans, appear to have been a major factor behind this trend. In Germany, where generous early retirement options were phased out after the mid-1990s, there is evidence that workers are paying a growing price for late-career job loss or health problems, which often lead to involuntary early retirement.
Additional information: Zugleich: Berlin, Freie Universität, Dissertation, 2013. Work on this book was partly conducted within a research project funded by the German Research Foundation (Deutsche Forschungsgemeinschaft; Grant # KO 2239/2). Publication was financially supported by the wzb Berlin Social Science Center (Wissenschaftszentrum Berlin für Sozialforschung).
Keywords: 330; welfare state change; older workers; retirement; Germany; United States